Sex-specific associations between blood urea nitrogen and risk of hyperuricemia in U.S. adults: the NHANES 1999-2020 - Chen, Lingling; Yin, Lixue (Frontiers in Endocrinology, 2025)
BackgroundBlood urea nitrogen (BUN), one of the recognized indicators of renal function, is a key marker of metabolic diseases, but there are few data on the association of BUN levels with hyperuricemia (HUA) in the general adult population. The aim of the study is to explore the relationship between BUN and HUA in the general population and the potential impact of gender on this relationship.MethodsThis study was conducted involving 17,846 adults from the National Health and Nutrition Examination Survey (NHANES) between 1999-2020. Data on age, gender, race, marital status, education level, height, weight, body mass index (BMI), waist circumference (WC), systolic blood pressure (SBP), diastolic blood pressure (DBP), triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), fasting plasma glucose (FPG), hemoglobin A1c (HbA1C), serum uric acid (SUA), BUN, creatinine, and albumin were collected from all participants. Multivariate logistic regression, curve fitting and subgroup analyses were employed to investigate the associations between BUN and HUA stratified by sex.ResultsAfter weighted analysis, the results of this study represented approximately 164.42 million U.S. adults. The overall prevalence of HUA was 18.22%, and 20.72% in males and 15.82% in females. In the fully adjusted model, there was a positive association between BUN and HUA and this positive association remained significantly stratified by sex. Smoothed curve-fitting analysis revealed that the dose-response relationship between BUN and the risk of developing HUA was linear in men and nonlinear in women. There was evidence of an interaction between BUN levels and gender status that increased the risk of HUA and the OR for the association between BUN and HUA was higher in females than in males. Subgroup analyses showed that the association between BUN and the risk of developing HUA remained consistently positive across all subgroups in both male and female participants.ConclusionsThis study confirmed that BUN were positively associated with HUA among U.S. adults that remained significant when stratified by sex, but there were gender differences in the form and extent of this positive correlation.